A simple model of mergers and innovation - Federico,G; Langus,G; Valletti,T (Economics Letters, 2017)
We analyze the impact of a merger on firms’ incentives to innovate. We show that the merging parties always decrease their innovation efforts post-merger while the outsiders to the merger respond by increasing their effort. A merger tends to reduce overall innovation. Consumers are always worse off after a merger. Our model calls into question the applicability of the “inverted-U” relationship between innovation and competition to a merger setting.